Typology and Morphology of Traditional House of Sumbersari Village Udanawu Blitar District - Iswanto, Heru Hendri; Sri Giriwati, Novi Sunu; Wikantiyoso, Respati (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2020)
Traditional houses in the village of Sumbersari are Javanese joglo houses that have been modified according to local culture. This traditional house is quite commonly found in Sumbersari Village, Udanawu District, Blitar, the distribution is quite evenly distributed in Blitar Regency. This traditional residence has the characteristics of the limasan building roof and has a symmetrical facade building, this residence belongs to a Javanese family with a higher status, so it has a uniqueness that is by the spatial layout and facade. Over time, only changes in spatial layout and facade are related to human needs, new technology, lifestyle, economic factors, inheritance, and cultural rights. With existence, traditional houses that are increasingly changing will eventually lose their identity. The purpose of this study is to analyze typologies by classifying traditional dwellings based on specific types and analyzing their morphology based on the level of change and the application of the changes. The method used is descriptive qualitative with a rationalistic discussion. The results of the studio are the data in the form of tables about the typology and morphology of traditional dwellings as the essence of the instructions for the form of traditional dwellings that can be contributed to the scientific architecture of the archipelago.Â DOI:Â https://doi.org/10.26905/lw.v12i2.3839